Cathepsin X in serum from patients with colorectal cancer: relation to prognosis - Vižin, Tjaša (Radiology and oncology (Ljubljana), 2012)
Background. Up-regulation of lysosomal cysteine protease cathepsin X (Cat X) is associated with disorders of the immune system and neurodegenerative diseases, while its role in the development and progression of cancer is less understood. Enhanced secretion of pro-Cat X was observed in malignant processes, and therefore, the level of total serum Cat X rather than the active enzyme may better reflect the tumour status. Patients and methods. Seventy-seven patients with colorectal cancer (CRC) were included in a retrospective study. Blood samples were collected prior to therapy. Using ELISA, the values of total Cat X were measured in serum. Groups of healthy persons (n=77), patients with adenomas (n=77) and patients with non-neoplastic findings (n=77) were included. Results. Significant differences between the group of colorectal patients and the groups of healthy persons, adenoma patients and patients with non-malignant findings could not be shown (p=0.89). Within the group of CRC, higher levels of total Cat X significantly correlated to shorter overall survival (HR=2.08, 95% CI:1.07-4.05, p=0.028). Conclusions. Total serum Cat X could be a useful prognostic indicator for determining survival of patients with CRC. Increased serum levels of total CatX may reflect more aggressive tumour cell phenotypes and suggest the involvement of Cat X in processes involved in later stages of tumour progression.
Keywords: cathepsin X; colorectal cancer; cysteine cathepsins; katepsin X; prognosis; prognoza; rak (medicina); serum biomarker